2019
DOI: 10.1016/j.jaci.2018.12.987
|View full text |Cite
|
Sign up to set email alerts
|

Defective glycosylation leads to defective gp130-dependent STAT3 signaling in PGM3-deficient patients

Abstract: To the Editor: Congenital disorders of glycosylation are a rare group of genetic disorders due to defects in protein glycosylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This phenotypic spectrum may potentially be dictated by the degree of impairment in PGM3 enzymatic function. 23 To date, 12 three of the more than 400 inborn errors of immunity (IEI) described are caused by glycosylation defects: PGM3 deficiency (OMIM 615816), MAGT1 deficiency, also known as X-linked immunodeficiency with magnesium defect, Epstein-Barr virus infection, and neoplasia (XMEN) (OMIM 300853) 24 and MAN2B2 deficiency 25 (Figure 1), the latter two being N-linked-CDG. As with other CDG disorders, the spectrum of manifestations is wide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotypic spectrum may potentially be dictated by the degree of impairment in PGM3 enzymatic function. 23 To date, 12 three of the more than 400 inborn errors of immunity (IEI) described are caused by glycosylation defects: PGM3 deficiency (OMIM 615816), MAGT1 deficiency, also known as X-linked immunodeficiency with magnesium defect, Epstein-Barr virus infection, and neoplasia (XMEN) (OMIM 300853) 24 and MAN2B2 deficiency 25 (Figure 1), the latter two being N-linked-CDG. As with other CDG disorders, the spectrum of manifestations is wide.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases with a more severe immunological phenotype resembling SCID 16,22 with or without severe congenital neutropenia 22 have also been reported. This phenotypic spectrum may potentially be dictated by the degree of impairment in PGM3 enzymatic function 23 …”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that mutations in PGM3 lead to a glycosylation defect in a rare form of HIES 16 . A more recent study demonstrated that defective glycosylation in PGM3‐deficient patients leads to reduced expression of the non‐glycosylated form of gp130 protein and thus to reduced gp130‐dependent STAT3 phosphorylation, explaining similar clinical features of PGM3 deficiency and the AD STAT3 form of the disease 18 . Despite the massive elevations of total IgE levels in various forms of HIES, little is known about the specificities of IgE in the affected patients.…”
Section: Introductionmentioning
confidence: 93%
“… 16 A more recent study demonstrated that defective glycosylation in PGM3‐deficient patients leads to reduced expression of the non‐glycosylated form of gp130 protein and thus to reduced gp130‐dependent STAT3 phosphorylation, explaining similar clinical features of PGM3 deficiency and the AD STAT3 form of the disease. 18 Despite the massive elevations of total IgE levels in various forms of HIES, little is known about the specificities of IgE in the affected patients. It has been even hypothesized that much of the IgE produced in PID patients is driven by dysregulated IL‐4 production and may lack antigen specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with biallelic loss-of-function variants in phosphoglucomutase 3 ( PGM3 ), present with an AR disorder including several features of classical HIES including increased serum IgE levels, recurrent skin and pulmonary infections, abscesses and bronchiectasis [ 38 , 39 , 40 ]. This can be partially explained by defective glycosylation of GP130 in theses patients causing lower GP130 surface expression and impaired STAT3 activation [ 41 ] ( Figure 2 ). However, defective glycosylation of GP130 is likely only one aspect of the PGM3 associated pathology.…”
Section: Defective Glycosylation Of Gp130 Due To Pgm3 Defectsmentioning
confidence: 99%